Endoscopic examination of the hepatic hydatic cavity.: Preliminary communication - Beguiristain, Alberto; Estefan, Alberto (Cirugía del Uruguay, 1995)
Endoscopicaf expforing of hepatic hydatic cavity with rigid choledoscopium is an additional procedure when choosing treatment far hepatic echinococcosis; it is simple, quick, and can be carried out by the surgeon in charge. lt can be done intra-operatively by way of the hydatic cyst or by way of the choledochus through the bilio-cystical fistula and post-operativefy through cystostomy tunnels.